Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Sure! Let's solve the problem step-by-step for both cases.
### Case 1: Finding [tex]\( n \)[/tex] such that the [tex]\( n \)[/tex]-th terms of the series [tex]\( 16, 14, 12, \ldots \)[/tex] and [tex]\( 22, 19, 16, \ldots \)[/tex] are equal.
The general form of an arithmetic sequence is:
[tex]\[ T_n = a + (n - 1) \cdot d \][/tex]
For the series [tex]\( 16, 14, 12, \ldots \)[/tex]:
- First term ([tex]\( a_1 \)[/tex]): 16
- Common difference ([tex]\( d_1 \)[/tex]): -2
The [tex]\( n \)[/tex]-th term ([tex]\( T_{n,1} \)[/tex]) is:
[tex]\[ T_{n,1} = 16 + (n - 1) \cdot (-2) \][/tex]
[tex]\[ T_{n,1} = 16 - 2(n - 1) \][/tex]
[tex]\[ T_{n,1} = 16 - 2n + 2 \][/tex]
[tex]\[ T_{n,1} = 18 - 2n \][/tex]
For the series [tex]\( 22, 19, 16, \ldots \)[/tex]:
- First term ([tex]\( a_2 \)[/tex]): 22
- Common difference ([tex]\( d_2 \)[/tex]): -3
The [tex]\( n \)[/tex]-th term ([tex]\( T_{n,2} \)[/tex]) is:
[tex]\[ T_{n,2} = 22 + (n - 1) \cdot (-3) \][/tex]
[tex]\[ T_{n,2} = 22 - 3(n - 1) \][/tex]
[tex]\[ T_{n,2} = 22 - 3n + 3 \][/tex]
[tex]\[ T_{n,2} = 25 - 3n \][/tex]
Setting [tex]\( T_{n,1} \)[/tex] equal to [tex]\( T_{n,2} \)[/tex]:
[tex]\[ 18 - 2n = 25 - 3n \][/tex]
Solving for [tex]\( n \)[/tex]:
[tex]\[ 18 - 2n = 25 - 3n \][/tex]
[tex]\[ 18 + n = 25 \][/tex]
[tex]\[ n = 25 - 18 \][/tex]
[tex]\[ n = 7 \][/tex]
So, the [tex]\( n \)[/tex]-th terms of the two series are equal when [tex]\( n = 7 \)[/tex].
### Case 2: Finding [tex]\( n \)[/tex] such that the [tex]\( n \)[/tex]-th terms of the series [tex]\( -9, -6, -3, \ldots \)[/tex] and [tex]\( 16, 14, 12, \ldots \)[/tex] are equal.
For the series [tex]\( -9, -6, -3, \ldots \)[/tex]:
- First term ([tex]\( a_3 \)[/tex]): -9
- Common difference ([tex]\( d_3 \)[/tex]): 3
The [tex]\( n \)[/tex]-th term ([tex]\( T_{n,3} \)[/tex]) is:
[tex]\[ T_{n,3} = -9 + (n - 1) \cdot 3 \][/tex]
[tex]\[ T_{n,3} = -9 + 3(n - 1) \][/tex]
[tex]\[ T_{n,3} = -9 + 3n - 3 \][/tex]
[tex]\[ T_{n,3} = 3n - 12 \][/tex]
For the series [tex]\( 16, 14, 12, \ldots \)[/tex]:
We already derived:
[tex]\[ T_{n,1} = 18 - 2n \][/tex]
Setting [tex]\( T_{n,3} \)[/tex] equal to [tex]\( T_{n,1} \)[/tex]:
[tex]\( 3n - 12 = 18 - 2n \)[/tex]
Solving for [tex]\( n \)[/tex]:
[tex]\[ 3n - 12 = 18 - 2n \][/tex]
[tex]\[ 3n + 2n = 18 + 12 \][/tex]
[tex]\[ 5n = 30 \][/tex]
[tex]\[ n = \frac{30}{5} = 6 \][/tex]
So, the [tex]\( n \)[/tex]-th terms of the two series are equal when [tex]\( n = 6 \)[/tex].
### Summary
- The [tex]\( n \)[/tex]-th terms of the series [tex]\( 16, 14, 12, \ldots \)[/tex] and [tex]\( 22, 19, 16, \ldots \)[/tex] are equal when [tex]\( n = 7 \)[/tex].
- The [tex]\( n \)[/tex]-th terms of the series [tex]\( -9, -6, -3, \ldots \)[/tex] and [tex]\( 16, 14, 12, \ldots \)[/tex] are equal when [tex]\( n = 6 \)[/tex].
### Case 1: Finding [tex]\( n \)[/tex] such that the [tex]\( n \)[/tex]-th terms of the series [tex]\( 16, 14, 12, \ldots \)[/tex] and [tex]\( 22, 19, 16, \ldots \)[/tex] are equal.
The general form of an arithmetic sequence is:
[tex]\[ T_n = a + (n - 1) \cdot d \][/tex]
For the series [tex]\( 16, 14, 12, \ldots \)[/tex]:
- First term ([tex]\( a_1 \)[/tex]): 16
- Common difference ([tex]\( d_1 \)[/tex]): -2
The [tex]\( n \)[/tex]-th term ([tex]\( T_{n,1} \)[/tex]) is:
[tex]\[ T_{n,1} = 16 + (n - 1) \cdot (-2) \][/tex]
[tex]\[ T_{n,1} = 16 - 2(n - 1) \][/tex]
[tex]\[ T_{n,1} = 16 - 2n + 2 \][/tex]
[tex]\[ T_{n,1} = 18 - 2n \][/tex]
For the series [tex]\( 22, 19, 16, \ldots \)[/tex]:
- First term ([tex]\( a_2 \)[/tex]): 22
- Common difference ([tex]\( d_2 \)[/tex]): -3
The [tex]\( n \)[/tex]-th term ([tex]\( T_{n,2} \)[/tex]) is:
[tex]\[ T_{n,2} = 22 + (n - 1) \cdot (-3) \][/tex]
[tex]\[ T_{n,2} = 22 - 3(n - 1) \][/tex]
[tex]\[ T_{n,2} = 22 - 3n + 3 \][/tex]
[tex]\[ T_{n,2} = 25 - 3n \][/tex]
Setting [tex]\( T_{n,1} \)[/tex] equal to [tex]\( T_{n,2} \)[/tex]:
[tex]\[ 18 - 2n = 25 - 3n \][/tex]
Solving for [tex]\( n \)[/tex]:
[tex]\[ 18 - 2n = 25 - 3n \][/tex]
[tex]\[ 18 + n = 25 \][/tex]
[tex]\[ n = 25 - 18 \][/tex]
[tex]\[ n = 7 \][/tex]
So, the [tex]\( n \)[/tex]-th terms of the two series are equal when [tex]\( n = 7 \)[/tex].
### Case 2: Finding [tex]\( n \)[/tex] such that the [tex]\( n \)[/tex]-th terms of the series [tex]\( -9, -6, -3, \ldots \)[/tex] and [tex]\( 16, 14, 12, \ldots \)[/tex] are equal.
For the series [tex]\( -9, -6, -3, \ldots \)[/tex]:
- First term ([tex]\( a_3 \)[/tex]): -9
- Common difference ([tex]\( d_3 \)[/tex]): 3
The [tex]\( n \)[/tex]-th term ([tex]\( T_{n,3} \)[/tex]) is:
[tex]\[ T_{n,3} = -9 + (n - 1) \cdot 3 \][/tex]
[tex]\[ T_{n,3} = -9 + 3(n - 1) \][/tex]
[tex]\[ T_{n,3} = -9 + 3n - 3 \][/tex]
[tex]\[ T_{n,3} = 3n - 12 \][/tex]
For the series [tex]\( 16, 14, 12, \ldots \)[/tex]:
We already derived:
[tex]\[ T_{n,1} = 18 - 2n \][/tex]
Setting [tex]\( T_{n,3} \)[/tex] equal to [tex]\( T_{n,1} \)[/tex]:
[tex]\( 3n - 12 = 18 - 2n \)[/tex]
Solving for [tex]\( n \)[/tex]:
[tex]\[ 3n - 12 = 18 - 2n \][/tex]
[tex]\[ 3n + 2n = 18 + 12 \][/tex]
[tex]\[ 5n = 30 \][/tex]
[tex]\[ n = \frac{30}{5} = 6 \][/tex]
So, the [tex]\( n \)[/tex]-th terms of the two series are equal when [tex]\( n = 6 \)[/tex].
### Summary
- The [tex]\( n \)[/tex]-th terms of the series [tex]\( 16, 14, 12, \ldots \)[/tex] and [tex]\( 22, 19, 16, \ldots \)[/tex] are equal when [tex]\( n = 7 \)[/tex].
- The [tex]\( n \)[/tex]-th terms of the series [tex]\( -9, -6, -3, \ldots \)[/tex] and [tex]\( 16, 14, 12, \ldots \)[/tex] are equal when [tex]\( n = 6 \)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.